La formación de ingenieros civiles: una experiencia con el ferrocarril del Nordeste y la doble calzada BTS (2016)
This article is the product of a study carried out at the university Santo Tomas in Tunja, regarding the restoration of the Northeast railroad and the training of civil engineers, which is done according to the method of other projects. Work has been done using this method and it has been found that the learning is truly extraordinary. It is observed that the percentage of retention is practically tripled for knowledge, motivation and dedication to creating knowledge. In this project we worked, from the perspective of a teacher, with two students, who devoted important time to the gathering of information, to its processing and analysis and to its verification. There is a clear need to restore the railroad, and in a short time rectify its route and widen the path, given that with studies on mobility, on accident rates, morbidity and mortality in the highway, in constant growth, there are many human, social, environmental, and economic losses being generated. Additionally it is estimated that around the year 2020, the divided highway will be saturated and it will be very expensive to carry out its expansion. The results were obtained based on field work, which was carried out in order to identify the current state of the railroad between Bogotá and Belencito, a stage of information gathering on historical data of vehicle mobility and accident rates registered in recent years, information on environmental pollution related to the emission of polluting agents, a product of fossil fuel use and its negative effects on the environment.